Uma análise exploratória dos diferenciais de salários entre carreiras de nível superior - Barbosa, Marcelo Ponte (2005)
This work carries through a exploratory analysis of the risk and return differentials between twenty higher education careers. As main source of data, it is used the Sample of the Demographic Census of the IBGE - 2000. At first, the influences of individual characteristics on wage differentials for each career are analyzed. Wage differentials between different demographic groups are explored using Mincer regressions. In a second moment, criterias that consider both risk and return are used to compare the distributions of wages. Tests of first and second orders stochastic dominance are applied to establish a ranking of the professions. The existence of a great heterogeneidade was evidenced between the careers in what concerns to the characteristics of the individuals. It was also evidenced the existence of a great differential of wages by gender, race/color and region. Wages for some careers go up more quickly with the experience and arrives at the equilibrium fastest than in others. Medicine dominates all other carriers while Pedagogy is fully dominated. The joined results suggest that, in order to be effective, higher education policies should consider the social-demographic composition and the profiles of returns of the different careers.